Genomic Comparison of Two Family-Level Groups of the Uncultivated NAG1 Archaeal Lineage from Chemically and Geographically Disparate Hot Springs - Becraft, Eric D.; Dodsworth, Jeremy A.; Murugapiran, Senthil K.; Thomas, Scott C.; Ohlsson, J. Ingemar; Stepanauskas, Ramunas; Hedlund, Brian P.; Swingley, Wesley D. (Frontiers in Microbiology, 2017)
ABSTRACT Recent progress based on single-cell genomics and metagenomic investigations of archaea in a variety of extreme environments has led to significant advances in our understanding of the diversity, evolution, and metabolic potential of archaea, yet the vast majority of archaeal diversity remains undersampled. In this work, we coordinated single-cell genomics with metagenomics in order to construct a near-complete genome from a deeply branching uncultivated archaeal lineage sampled from Great Boiling Spring (GBS) in the U.S. Great Basin, Nevada. This taxon is distantly related (distinct families) to an archaeal genome, designated “Novel Archaeal Group 1” (NAG1), which was extracted from a metagenome recovered from an acidic iron spring in Yellowstone National Park (YNP). We compared the metabolic predictions of the NAG1 lineage to better understand how these archaea could inhabit such chemically distinct environments. Similar to the NAG1 population previously studied in YNP, the NAG1 population from GBS is predicted to utilize proteins as a primary carbon source, ferment simple carbon sources, and use oxygen as a terminal electron acceptor under oxic conditions. However, GBS NAG1 populations contained distinct genes involved in central carbon metabolism and electron transfer, including nitrite reductase, which could confer the ability to reduce nitrite under anaerobic conditions. Despite inhabiting chemically distinct environments with large variations in pH, GBS NAG1 populations shared many core genomic and metabolic features with the archaeon identified from YNP, yet were able to carve out a distinct niche at GBS.